Secondary ameloblastic carcinoma in the midline of the mandible: A case report and literature review. Issue 2 (March 2020) - Ohira, Memi; Kawahara, Kou; Oriyama, Tasuku; Oguri, Takashi; Shibata, Akio; Miyabe, Satoru
Abstract: Ameloblastic carcinoma is rare type of cancer and is classified into two types: primary and secondary. The latter type is extremely rare with few cases being reported till date. Here, we report the case of a 61-year-old male with a large secondary ameloblastic carcinoma of the mandible. Although malignant findings were clinically observed, histopathologically, the biopsy revealed ameloblastoma with no evidence of malignancy. The mandible was also segmentally resected. Postoperatively, a diagnosis of ameloblastic carcinoma was pathologically established. Fortunately, 5.5 years after the surgery, no evidence of recurrence or metastasis was observed. We suggest that when malignancy is clinically considered, multiple tissue biopsies should be obtained from patients with odontogenic tumors.